Trauma, Tumors, Spine, Functional Neurosurgery - Signorelli, Francesco (IntechOpen, 2016)
This book is written for graduate students, researchers, and practitioners who are interested in learning how the knowledge from research can be implemented in clinical competences. The first section is dedicated to deep brain stimulation, a surgical procedure which is the paramount example of how clinical practice can take advantage from fundamental research. The second section gathers four chapters on four different topics and illustrates how significant is the challenge to translate scientific advances into clinical practice because the route from evidence to action is not always obvious. It is hoped that this book will stimulate the interest in the process of translating research into practice for a broader range of neurosurgical topics than the one covered by this book, which could result in a forthcoming more comprehensive publication.